Bauran Pemasaran Jasa Dan Minat Berkunjung Kembali (Studi Pada Kedai Kopi "Cerita Kopi Xotus" Telang Bangkalan) - Ulwiyah, Ulwiyah; Syarif, Muhammad (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This research is entitled "Marketing Mix of Services and Revisit Intention (Study of the Coffee Shop"Cerita Kopi Xotus"Telang Bangkalan)". place, promotion, process, physical evidence and people so that they can attract customers to be revisiting intention the Xotus Telang coffee shop, Bangkalan. This research was conducted descriptively quantitatively using purposive sampling method, namely the technique of determining the sample by considering certain criteria with a total sample of 97 respondents. The data analysis technique used is multiple linear regression analysis.Based on the results of the analysis, it shows that the customer's interest in returning to the Xotus Telang Bangkalan coffee shop is in the good category. And the marketing mix is also in a good category. so that it can trigger an revisit intention customers. And the results of the espionage of several service marketing mix variables show that the product has a significant effect on the revisit intention to the Xotus Telang Bangkalan coffee shop. Price has no significant effect on revisit intention to the Xotus Telang coffee shop Bangkalan. Promotion has a significant effect on the revisit intention to the Xotus Telang Bangkalan coffee shop. Place has a significant effect on revisit intention to Xotus Telang Bangkalan coffee shop. People have no significant effect on the revisit intention to the Xotus Telang Bangkalan coffee shop. Physical evidence has no significant effect on the revisit intention to the Xotus Telang Bangkalan coffee shop. The process has no significant effect on the revisit intention to the Xotus Telang coffee shop Bangkalan. Product, Price, Promotion, Place, People, Physical Evidence, Process together have a significant effect on revisit intention to Xotus Telang Bangkalan coffee shop. Keyword : Marketing Mix, Revisit Intention, Coffe shop Xotus Telang Bangkalan